2021
DOI: 10.1002/pan3.10192
|View full text |Cite
|
Sign up to set email alerts
|

To tell a different story: Unexpected diversity in local attitudes towards Endangered Aye‐ayes Daubentonia madagascariensis offers new opportunities for conservation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 96 publications
(187 reference statements)
0
9
0
1
Order By: Relevance
“…A recent study, however, revealed the heterogeneity in local attitudes toward aye-ayes across 11 villages in northern Madagascar (Randimbiharinirina et al, 2021). The researchers found that negative attitudes toward aye-ayes in some villages stemmed from vague accounts unfounded in the ecology of this lemur species, while positive and neutral attitudes in other villages were based on the observed behavior of aye-ayes as providers of pest-control services and curiosity about the species (B3; C3) (Randimbiharinirina et al, 2021). The identification of this variable social-ecological relationship across the study area provides opportunities for targeted conservation initiatives that highlight the beneficial value of aye-ayes as providers of pestcontrol services, and offers a nuanced approach that considers local and site-specific values.…”
Section: The Role Of Informal Institutionsmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent study, however, revealed the heterogeneity in local attitudes toward aye-ayes across 11 villages in northern Madagascar (Randimbiharinirina et al, 2021). The researchers found that negative attitudes toward aye-ayes in some villages stemmed from vague accounts unfounded in the ecology of this lemur species, while positive and neutral attitudes in other villages were based on the observed behavior of aye-ayes as providers of pest-control services and curiosity about the species (B3; C3) (Randimbiharinirina et al, 2021). The identification of this variable social-ecological relationship across the study area provides opportunities for targeted conservation initiatives that highlight the beneficial value of aye-ayes as providers of pestcontrol services, and offers a nuanced approach that considers local and site-specific values.…”
Section: The Role Of Informal Institutionsmentioning
confidence: 96%
“…Moreover, we scanned for articles fitting our key terms in all volumes published in Lemur News (Volumes 1-22; years 1996-2019/20), the newsletter of the Madagascar section of the IUCN/SSC Primate Specialist Group (http:// www.primate-sg.org/lemur_news/). Two references, a global overview of the use of primates in traditional medicine (Alves et al, 2010) and a recent study on local attitudes toward ayeayes (Daubentonia madagascariensis) (Randimbiharinirina et al, 2021), were not part of the original search results but were included in the review. Our search resulted in 51 total papers used for a content analysis (see Supplementary Table 1 for a complete list of references).…”
Section: Literature Search and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In Madagascar, population restoration [sensu Seddon et al, 2012] programs of lemurs have been carried out to reinforce existing populations or to repopulate areas where species have been locally extirpated [Britt et al, 2004;Day et al, 2009]. The threats and pressures that lemurs face include habitat loss through deforestation (slash and burn agriculture and selective logging), illegal poaching for food and the pet trade, and hunting due to fear or fady (i.e., a cultural taboo) [Sterling and Feistner, 2000;Simons and Meyers, 2001;Sterling, 2003;Glaw et al, 2008;Louis et al, 2020, Randimbiharinirina et al, 2021. These programs can help rehabilitate or support vulnerable populations in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the ecology of D. madagascariensis have been carried out in the eastern rain forests of Madagascar [Petter and Peyrieras, 1970;Iwano and Iwakawa, 1988;Iwano, 1991;Sterling, 1993a, b;Ancrenaz et al, 1994;Erickson, 1995;Farris et al, 2011;Sefczek et al, 2012;Sedera, 2014;Solofondranohatra, 2014;Randimbiharinirina, 2015;Thompson et al, 2016;Sefczek et al, 2017;Randimbiharinirina et al, 2018, Sefczek et al, 2020aRakotondrazandry et al, 2021;Randimbiharinirina et al, 2021]. In these habitats, aye-ayes have been reported to feed on insects and larvae, fruits and seeds [Andriamasimanana, 1994], nectar and flowers [Sterling, 1993;Ancrenaz et al, 1994;Sterling, 1993b], bamboo shoots and outgrowths on trees [Pollock et al, 1985;Sterling and McCreless, 2006].…”
Section: Introductionmentioning
confidence: 99%